THE MODERATING IMPACT OF COMMUNITY SUPPORT ONTRI-DIMENSIONAL IMPACTS OF TOURISM (ECONOMIC, SOCIO-CULTURAL, & ENVIRONMENTAL) TOWARDS RURAL TOURISM COMPETITIVE ADVANTAGE - Lim, Jason; Lo, May Chiun; Abang Azlan, Mohamad; Chin, Chee Hua; Ramayah, T. (2017)
Rural tourism being one of most influencing industries in Malaysia, in particular, the state of Sarawak.Competitiveness to a host destination especially in rural tourism has always be a concern to the stakeholders. As a result, increase competitive advantage to a host destination is somehow necessary if rural tourism is valued and to be invested for future development.Thus, the theory of resource based view underpins the proposed research framework and intends to investigate the influence of tri-dimensional impacts on rural tourism competitive advantagefrom local communities’ perspectives. This is the first known study to adopt community support as the moderating variable to examine the proposed constructs. A total of 222 respondentswere used for statistical analysis. To assess the developed model, SmartPLS (version 3.2.6) is applied based on path modeling and then bootstrapping. The results revealed that socio-cultural impacts and environmental impactsare significantly and positively correlated to rural tourism competitive advantagefrom the communities’ perspectives.As per expectation, the findings also revealed that community support exists in moderating the relationship among environmental impacts and rural tourism destination competitive advantage.